(untitled) (Innovative professional education, 2025)
The article examines the use of project technology in the process of studying general education disciplines. The advantages of project-based learning, its implementation features, and its impact on the formation of students’ competencies are analyzed. The prospects for the introduction of the project method in the modern educational system of Ukraine are determined